Chemomechanics of dual-stage reprocessable thermosets. (May 2019) - Luo, Chaoqian; Zhang, Biao; Zhang, Wang; Yuan, Chao; Dunn, Martin; Ge, Qi; Yu, Kai
Abstract: The recently developed dual-stage 3D printing reprocessable thermosets (3DPRTs) utilize acrylate functional groups to enable the ultra-violet based 3D printing (Stage I), and employ bond exchange reaction (BERs) to tailor the network structure for mechanical properties enhancement and impart the reshapeability, reparability, and recyclability into traditionally unprocessable thermosets (Stage II). 3DPRT provides a practical solution to address environmental challenges associated with the rapid increase in the consumption of 3D printing materials. However, due to the nascent state of development, fundamental understanding of the chemomechanics during the processing of 3DPRTs is still lacking. In this paper, we present detailed experimental and theoretical studies to understand the effect of thermal treatment condition at Stage II on the evolution of network structure and thermomechanical properties of 3DPRTs. A chemomechanics theory is defined to link the molecular-level BER kinetics to the macroscale thermomechanical properties of 3DPRTs during the thermal treatment. A thermo-viscoelastic multi-branched constitutive model is then established to capture the elastic and glass transition behaviors during the Stage II processing. The developed theory is able to capture the experimental observations on the mechanical properties enhancement and provide theoretical guidance for the network design and the selection of thermal treatment conditions to tailor the final mechanical properties of 3DPRTs.